The role of detoxification enzymes in the susceptibility of Brevipalpus californicus exposed to acaricide and insecticide mixtures - Della Vechia, Jaqueline F. [UNESP]; Van Leeuwen, Thomas; Rossi, Guilherme D. [UNESP]; Andrade, Daniel J. [UNESP] (Elsevier, 2021)
The intense spraying of pesticides to control different arthropod pests has resulted in negative side effects for the management of pests. It was previously discovered that exposure to non-acaricidal insecticides alone or in a mixture, results in lower efficiency of the acaricide spirodiclofen used for Brevipalpus spp. control. We investigate here whether the induced expression of detoxification enzymes by non-lethal insecticides may antagonize spirodiclofen toxicity. Brevipalpus californicus mites exposed to the insecticide phosmet alone or in combination with spirodiclofen showed increased activity of P450 monooxygenases (P450s). No antagonistic effects in mite mortality were observed by the combination of phosmet and spirodiclofen. On the other hand, mites exposed to the insecticide imidacloprid alone or in combination with spirodiclofen showed an increase in the activity of P450s, carboxylcholinesterases (CCE), and glutathione-S-transferases (GST). An antagonistic effect on mite mortality was observed when mites were exposed to the LC25 of spirodiclofen combined with the field rate treatment of imidacloprid. The addition of PBO (a P450 monooxygenase inhibitor) to the mixture of spirodiclofen and imidacloprid resulted in a synergistic effect over mite mortality but the addition of DEM (a GST inhibitor) resulted in an antagonist effect. Taken together, this study showed that the combination of imidacloprid with spirodiclofen is antagonistic for the control of B. californicus, and this results from the induction of detoxification enzymes, such as P450s, CCE, and GST. The use of inhibitors highlights the role of these enzymes in the antagonism of the mixture.
Keywords: Antagonism; Esterases; GST; Metabolism; Monooxygenases; Synergism